301 BENEFITS OF ENVIRONMENTAL MUSIC THERAPY IN AN ACUTE HOSPITAL. (25th October 2022) - Cassidy, M; Hayes, R; Nevin, R; Griffin, A; Herbst, J; Mealy, B; Walsh, K; Donnelly, R; Harrison, H; Jariol, A; Joseph, L; Carroll, KM
Abstract: Background: Environmental Music Therapy (EMT) uses live music played by a music therapist to enhance the surrounding environment and is increasingly used in clinical settings. Studies show that EMT may reduce anxiety, enhance wellbeing, promote better communication between patients and staff, and reduce patient perception of waiting times in hospital. We aimed to explore the benefit of EMT for older adults in a geriatric outpatient setting and on rehabilitation wards. Methods: Harp music was played by a music therapist in the vicinity of ambulatory clinics and on rehabilitation wards for 4 hours per week (over a 2-day period) for 20 weeks. Music exposure on any given day was to an estimated 50 outpatients, as well as 50 people passing the vicinity or to about 30 patients on the rehabilitation ward. Music was selected and played in a dynamic process, responding to verbal and non-verbal reactions of patients, family, and staff. Voluntary responses were recorded and collated. Results: There were 36 recorded responses and all reflected positively on EMT. Patients cited that the music created a welcoming space and stimulated interaction and conversation. Several patients waiting for their clinic appointment noted that it distracted from fearful expectation and was a source of comfort. Some commented that they felt more relaxed and that it reduced stress. On rehabilitation wards, patients found familiar music to be calming with nurses citing that it stimulated social interaction between patients, family and staff. Responses to EMT gave insights that resulted in patient referrals for music therapy. Conclusion: Environmental music played by a music therapist was found to modify patient hospital experiences. In particular, it appeared to reduce self-perceived stress and stimulate positive social interaction and conversation. This supports the use of EMT to advance the integration of the arts for wellbeing in an acute hospital.